The Identification of Collagen Messenger RNA - Boedtker, Helga (1974)
RNA isolated from calvaria of 16- to 18- day-old chick embryos, assayed in rabbit reticulocyte lysates, programs the synthesis of a collagenase-sensitive protein with the molecular weight of collagen pro-α-chains. When RNA labeled with [(3)H]uridine for 2 hr and chased for 1 or 2 hr was electrophoresed on aqueous polyacrylamide gels, most of the radioactivity not in 28S or 18S rRNA migrated with an apparent molecular weight of about 1,800,000. After oligo(dT)-cellulose chromotography and analysis in 99% formamide gels, this nonribosomal, rapidly labeled calvaria RNA species migrates at 28S-30S and thus has a molecular weight of at least 1,600,000. Both the ability to program the synthesis of collagenase-sensitive protein in reticulocyte lysates and the presence of a single prominent rapidly labeled 30S peak in acrylamide gels strongly support the deduction that there is only one major mRNA species in calvaria and that this species is collagen messenger RNA.